Sustained Intraocular Pressure Elevation After Intravitreal Injection of Bevacizumab and Ranibizumab Associated with Trabeculitis - Sniegowski, Matthew (Bentham Open, 2010)
Anti-vascular endothelial growth factor agents are frequently used to treat a variety of ocular neovascular diseases. While agents like bevacizumab and ranibizumab appear to be safe and effective, there have been reports of severe intraocular inflammation as well as sustained elevation of intraocular pressure (IOP) after single or multiple intravitreal injections of these protein-based therapeutics. The true mechanism leading to inflammation and/or sustained spikes in IOP remains unknown. We report a patient with sustained IOP elevation and kerato-precipitates on the trabecular meshwork after multiple injections of both bevacizumab and ranibizumab. We propose that monomer antibodies, aggregated proteins, or other high molecular weight molecules might lead to inflammation in the trabecular meshwork and subsequent elevation in IOP.